Quasi-Exactly Solvable Schrödinger Operators in Three Dimensions - Fortin Boisvert, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
The main contribution of our paper is to give a partial classification of the quasi-exactly solvable Lie algebras of first order differential operators in three variables, and to show how this can be applied to the construction of new quasi-exactly solvable Schrödinger operators in three dimensions.